ANALISIS KEPUASAN KERJA PEGAWAI BPJS KETENAGAKERJAAN CABANG BALIKPAPAN - Imam Arywibowo; Tutik Yuliani; Wanda Putri (Jurnal GeoEkonomi, 2023)
The purpose of this study was to determine the effect of compensation, leadership, and work discipline on job satisfaction of employees of the Balikpapan Branch of Employment BPJS, with 43 respondents, this research method uses quantitative methods. Data collection by distribution of google form questionnaires. The data analysis technique used is multiple linear analysis by conducting instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the variables of compensation, leadership, and work discipline had a positive and significant effect on job satisfaction of the Balikpapan Branch of Employment BPJS.